Schwann Cells in Neuromuscular Junction Formation and Maintenance - Barik, Arnab (J Neurosci, 2016)
The neuromuscular junction (NMJ) is a tripartite synapse that is formed by motor nerve terminals, postjunctional muscle membranes, and terminal Schwann cells (TSCs) that cover the nerve-muscle contact. NMJ formation requires intimate communications among the three different components. Unlike nerve-muscle interaction, which has been well characterized, less is known about the role of SCs in NMJ formation and maintenance. We show that SCs in mice lead nerve terminals to prepatterned AChRs. Ablating SCs at E8.5 (i.e., prior nerve arrival at the clusters) had little effect on aneural AChR clusters at E13.5, suggesting that SCs may not be necessary for aneural clusters. SC ablation at E12.5, a time when phrenic nerves approach muscle fibers, resulted in smaller and fewer nerve-induced AChR clusters; however, SC ablation at E15.5 reduced AChR cluster size but had no effect on cluster density, suggesting that SCs are involved in AChR cluster maturation. Miniature endplate potential amplitude, but not frequency, was reduced when SCs were ablated at E15.5, suggesting that postsynaptic alterations may occur ahead of presynaptic deficits. Finally, ablation of SCs at P30, after NMJ maturation, led to NMJ fragmentation and neuromuscular transmission deficits. Miniature endplate potential amplitude was reduced 3 d after SC ablation, but both amplitude and frequency were reduced 6 d after. Together, these results indicate that SCs are not only required for NMJ formation, but also necessary for its maintenance; and postsynaptic function and structure appeared to be more sensitive to SC ablation. SIGNIFICANCE STATEMENT Neuromuscular junctions (NMJs) are critical for survival and daily functioning. Defects in NMJ formation during development or maintenance in adulthood result in debilitating neuromuscular disorders. The role of Schwann cells (SCs) in NMJ formation and maintenance was not well understood. We genetically ablated SCs during development and after NMJ formation to investigate the consequences of the ablation. This study reveals a critical role of SCs in NMJ formation as well as maintenance.